Impact of Rapid Urbanization, Climate Change, and Drainage Design on Urban Flash Floods in New Cairo, Egypt - Hassan, Bassma Taher (AUC Knowledge Fountain, 2022)
Urban flooding is considered one of the most hazardous disasters in metropolitan areas, which causes growing risk on people’s lives, infrastructure and environment. Egypt witnessed an unprecedent extreme rainfall event in 2020 that caused more than four hundred injuries and major damage in properties and infrastructures affecting the economic and social aspects adversely. This was not the first extreme rainfall event causing catastrophic implications, over the past 5 years, New Cairo have been experiencing intense rainfall events almost every year that put the community in jeopardy. This research intends to investigate the main drivers prompting urban flash floods in New Cairo; particularly, the effects of rapid urbanization, climate change and drainage design on the surface runoff. The rainfall analysis is conducted over the period of 2000 to 2020 using Global Precipitation Measurement (GPM), which had the best rainfall measurements within six satellite rainfall products and ground rainfall data. The spatial urban sprawl is assessed through runoff simulations of seven land use maps between 1990 to 2020. Watershed Management System (WMS) simulation indicated that the rapid urban expansion in the area led to an increase in the total runoff of about 180%. On the other hand, the potential effect of climate change on urban flash floods was investigated through comparing ground observed storm data with six bias corrected climate change scenarios. Storm intensities in New Cairo seemed to reasonably agree with climate change precipitation scenario CNRM4.5. Finally, an actual drainage load-capacity balance during storm events was evaluated for seventeen neighborhoods in New Cairo. The analysis suggested that poor drainage capacities might have caused a significant increase in the surface runoff during storm events causing the flash floods. The research suggests that upgrading the current pump stations and planning emergency pumping strategies during storm events may effectively mitigate New Cairo’s flooding problem.